2001
DOI: 10.1097/00006982-200104000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Rhegmatogenous Retinal Detachment

Abstract: In this series, pediatric RRD occurred most commonly in association with myopia (Stickler's syndrome and adolescent retinopathy of prematurity) and prior intraocular surgery. Most eyes were anatomically reattached after multiple surgeries. Forty-one percent of eyes retained vision of 20/800 or better. Preserving vision in children with RRD is of great importance, particularly given the 89% frequency of vision-threatening abnormalities in fellow eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
97
1
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 6 publications
15
97
1
15
Order By: Relevance
“…Only 40-70% of patients report symptoms at the time of diagnosis. 2,11,12 As expected, this percentage is even less in younger age groups. Hence, children with retinal detachments are more likely to present with fluid under the macula and with proliferative vitreoretinopathy (PVR) ( Table 1).…”
Section: Presenting Characteristicssupporting
confidence: 76%
See 2 more Smart Citations
“…Only 40-70% of patients report symptoms at the time of diagnosis. 2,11,12 As expected, this percentage is even less in younger age groups. Hence, children with retinal detachments are more likely to present with fluid under the macula and with proliferative vitreoretinopathy (PVR) ( Table 1).…”
Section: Presenting Characteristicssupporting
confidence: 76%
“…1 Pediatric RRD is much less common, with an annual incidence only 0.38-0.69 per 100,000, 2 making up only 0.5-8% of all retinal detachments. [2][3][4][5][6][7][8][9] A number of case series of pediatric RRD have been reported (Table 1). [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Most of these case series include patients up to 18 years of age and the mean or median ages of presentation that are reported are 9-13 years of age.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In our study group, In all 22% of eyes in this study presented with grade C or D PVR. Likewise, several studies of paediatric RRD also reported a high rate of PVR, attributed to delayed diagnosis 4,5 and increased intraocular cellular activity. 2 Complete retinal reattachment was achieved only in 42% of PVR cases in this study, and the functional results were worser than the anatomical results.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical features of paediatric RRD are different from those of adults because of delayed diagnosis due to poor subjective complaints 4,5 and an association with various complicating entities. [1][2][3]5 Extrapolation of data obtained from adult cases, therefore, may be inappropriate for the management of paediatric RRD. Instead, data from clinical study focusing on paediatric cases are required.…”
Section: Introductionmentioning
confidence: 99%